Public knowledge of deforestation in Sik, Kedah - Saiful Haifiz, Muhd Solihin (2019)
Knowledge can be referred as to the condition of knowing something. Knowledge can be information, facts, principles, skills and understanding on something that acquire through education or experience. This study is carried out to determine the level of public knowledge on deforestation. A total of, 234 respondents were interviewed from five villages in Sik, Kedah. A questionnaire was used to collect information on demographic data and knowledge of the deforestation. The demographic section includes gender, household income, education level, and participation on association related to environment. The knowledge on deforestation includes definition, impact of deforestation and factors contributed to deforestation. The result reveals, that the people in Sik have a little knowledge on deforestation. As for the environment concern, most of the people in Sik are more concerned on urban development than deforestation. Education and campaign for the new generation should be extended to the local communities to enhance their knowledge and awareness toward deforestation.